Konsep Perpajakan dalam Pemikiran Al-Mawardi dan Implementasinya dalam Sistem Ekonomi Islam - Noval Muhammad Zaini, Noval; Muhammad Zahran Hidayatul Urfa; Asep Kurniawan; Lina Marlina (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This study discusses the concept of taxation in Al-Mawardi's thought and its implementation in the Islamic economic system. Al-Mawardi, in his work Al-Ahkam As-Sultaniyyah, explains that taxes in Islam have a foundation of justice and public benefit. The types of taxes he discussed include zakat, kharaj, jizyah, and usyur, each of which has the aim of maintaining economic stability and social welfare. This research uses a qualitative method with a literature study approach. The results show that the concept of taxation in Islam focuses more on social balance compared to the conventional taxation system. Al-Mawardi emphasized that taxes must be collected fairly and transparently and used for the public interest to avoid economic inequality. The findings indicate that the principles of taxation in Al-Mawardi's thought are still relevant to the modern taxation system, especially in the aspects of justice, wealth distribution, and tax accountability.